2022
DOI: 10.3389/fimmu.2022.986085
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of anti-S immune response at 6 months after COVID-19 vaccination in a multicentric European cohort of healthcare workers – ORCHESTRA project

Abstract: BackgroundThe duration of immune response to COVID-19 vaccination is of major interest. Our aim was to analyze the determinants of anti-SARS-CoV-2 IgG titer at 6 months after 2-dose vaccination in an international cohort of vaccinated healthcare workers (HCWs).MethodsWe analyzed data on levels of anti-SARS-CoV-2 Spike antibodies and sociodemographic and clinical characteristics of 6,327 vaccinated HCWs from 8 centers from Germany, Italy, Romania and Slovakia. Time between 1st dose and serology ranged 150-210 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 44 publications
(69 reference statements)
6
24
0
Order By: Relevance
“…Several studies have demonstrated the lower levels of immunological responsiveness of older subjects ( 16 ). This is consistent with our previous study that showed age as a determinant of lower level of serologic response in HCW ( 11 ). When focusing on gender differences, a 2% smaller probability of undergoing a one standard error decrease in antibody level was suggested for women, consistent with previous literature ( 17 19 ).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Several studies have demonstrated the lower levels of immunological responsiveness of older subjects ( 16 ). This is consistent with our previous study that showed age as a determinant of lower level of serologic response in HCW ( 11 ). When focusing on gender differences, a 2% smaller probability of undergoing a one standard error decrease in antibody level was suggested for women, consistent with previous literature ( 17 19 ).…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies focused on HCW as a job category rather than distinguishing potential association with COVID-19 infection and vaccination outcomes. For example, in a previous analysis we once again found no relationship between job title and immunological response ( 11 ). Moreover, a previous study based on the Italian cohort of the ORCHESTRA project found no difference in the risk of HCW contracting COVID-19, even when considering HCW in departments dedicated to COVID-19 ( 22 ).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations